Quasi-dark trading: The effects of banning dark pools in a world of many alternatives - Thomas Johann; Talis Putnins; Satchit Sagade; Christian Westheide (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
We show that "quasi-dark" trading venues, i.e., markets with somewhat non-transparent trading mechanisms, are important parts of modern equity market structure alongside lit markets and dark pools. Using the European MiFID II regulation as a quasi-natural experiment, we find that dark pool bans lead to (i) volume spill-overs into quasi-dark trading mechanisms including periodic auctions and order internalization systems; (ii) little volume returning to transparent public markets; and consequently, (iii) a negligible impact on market liquidity and short-term price efficiency. These results show that quasi-dark markets serve as close substitutes for dark pools and consequently mitigate the effectiveness of dark pool regulation. Our findings highlight the need for a broader approach to transparency regulation in modern markets that takes into consideration the many alternative forms of quasi-dark trading.
urn:nbn:de:hebis:30:3-504422
Keywords: G10; G19; 330; Dark Pools; Dark Trading; Liquidity; Price Efficiency; MiFID II; Double VolumeCaps